Health‐related quality of life in long‐term prostate cancer survivors after nerve‐sparing and non‐nerve‐sparing radical prostatectomy—Results from the multiregional PROCAS study. (10th June 2020) - Adam, Salome; Martin‐Diener, Eva; Camey, Bertrand; Egger Hayoz, Céline; Konzelmann, Isabelle; Mohsen Mousavi, Seyed; Herrmann, Christian; Rohrmann, Sabine; Wanner, Miriam; Staehelin, Katharina; Strebel, Räto T.; Randazzo, Marco; et al.
Abstract: Background: Nerve‐sparing (NS) surgery was developed to improve postoperative sexual and potentially urological outcomes after radical prostatectomy (RP). However, it is largely unknown how NSRP affects health‐related quality of life (HRQoL) including urinary and sexual outcomes in prostate cancer (PC) survivors 5‐10 years after diagnosis in comparison with Non‐NSRP. Methods: The study population included 382 stage pT2‐T3N0M0 PC survivors 5‐10 years post diagnosis, who were identified from the multiregional Prostate Cancer Survivorship in Switzerland (PROCAS) study. Briefly, in 2017/2018, PC survivors were identified via six population‐based cancer registries based in both German‐ and French‐speaking Switzerland. HRQoL and PC‐specific symptom burden was assessed using the EORTC QLQ‐C30 and EORTC QLQ‐PR25 questionnaires. Differences in HRQoL outcomes between survivors treated with NSRP (uni‐ & bilateral) and Non‐NSRP were analyzed with multivariable linear regression adjusted for age, years since diagnosis, cancer stage, comorbidities at diagnosis, and further therapies, if appropriate. Multiple imputation was performed to minimize the bias due to missing data. Results: Five to ten years after diagnosis, PC survivors treated with NSRP and Non‐NSRP reported similar symptom burden and comparable HRQoL function scores. The only significant differences were reported for sexual activity, whereas PC survivors who underwent NSRP reported statistically significant ( P  = .031) higher sexual activity than those on Non‐NSRP. NSRP and Non‐NSRP reported similar scores for urinary symptoms and all other HRQoL outcomes. Conclusions: Our results support nerve‐sparing techniques as an option to improve postoperative sexual, but not urinary outcomes after RP in long‐term PC survivors. Abstract : Nerve‐sparing radical prostatectomy and non‐nerve‐sparing radical prostatectomy were generally associated with comparable long‐term health‐related quality of life outcomes, but nerve‐sparing radical prostatectomy was linked with significantly higher sexual activity scores than non‐nerve‐sparing radical prostatectomy. Our results support nerve‐sparing techniques as an option to improve postoperative sexual but not urinary outcomes after radical prostatectomy in long‐term prostate cancer survivors.